Growth and physiology of seedlings of the tree species Copaifera langsdorffii desf. treated with haloxyfop-p-methyl - G. C. Santos; I. M. Pereira; G. M. Barroso; E. A. Ferreira; J. B. Santos (Brazilian Journal of Biology)
Abstract One of the biggest challenges in reforestation or restoration with native tree species has been the presence of invasive grasses. Chemical control can be a solution as long as the impacts of herbicides are adequately evaluated through studies of the effects of these products on the environment and non-target organisms. In this sense, the objective was to evaluate the effect of doses of the graminicide haloxyfop-p-methyl on seedlings of the Copaifera langsdorffii Desf. The experiment was installed in a climate-controlled greenhouse of the Department of Forestry Engineering of the Federal University of the Jequitinhonha and Mucuri Valleys and conducted in a randomized block design (RBD) with 60 healthy individuals of C. langsdorffii. The experiment was installed in May 2018 and conducted for approximately 120 days. The treatments comprised herbicide doses (0, 30, 60 and 120 g ha-1). The variables analyzed were visual intoxication, total chlorophyll, chlorophyll a fluorescence, number of leaves and leaflets, increases in height and diameter, and survival. No symptoms of intoxication were observed in the plants throughout the experiment period. Haloxyfop-p-methyl did not influence plant physiology or growth. C. langsdorffii seedlings were not sensitive to the herbicide. The plants were tolerant to the graminicide haloxyfop-p-methyl. Therefore, this herbicide can be used to control grasses in areas under forest restoration without harming the tree species studied.